Status ekologi hutan mangrove pada berbagai tingkat ketebalan - Heru Setiawan (Jurnal Penelitian Kehutanan Wallacea, 2013)
This research was aimed to know the ecological condition of mangrove forest at various thickness levels and its influence on salinity of fresh water at surrounding area. This research was conducted by analysis of sea water, fresh water, plankton, substrate (soil), and makrobenthos at three location, those were: (1) mangrove with high thickness level (200-300 metre) in Tongke-Tongke Village, (2) mangrove with middle thickness level in Panaikang Village and (3) location without mangrove in Pasimarannu Village. The result of analysis showed that the rate of DO and BOD of seawater in Tongke-Tongke were 5,76 ppm and 1,68 ppm, Panaikang village were 6,48 ppm and 3,63 ppm and Pasimarannu village 6,72 pm and 3,36 ppm. Based on fresh water analysis, the ecosystem of mangrove has significant influence to reduce salinity level. The salinity of fresh water in location with highest thickness level is lowest (Tongke-Tongke is 2.2 ppt) compared to others (Panaikang 2.4 ppt and Pasimarannu 3.2 ppt). The result of substrat analysis showed similar result in which the highest organic substance rate is in Tongke-Tongke followed by Panaikang and Pasimarannu. Abundance of plankton and makrobentos in location with highest thickness level is highest (Tongke-Tongke 210 individu/ml and 849 individu/m2) compared to others (Panaikang is 202 individual/ml and 815 individu/m2 and Pasimarannu village 132 individu/ml and 320 individu/m2)